KEPENTINGAN EKONOMI DAN POLITIK INDONESIA BEKERJA SAMA DENGAN SLOVAKIA DALAM EKSPOR CPO (Crude Palm Oil) - Santi Silalahi; Tri Joko Waluyo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study will describe the economic and political interests of Indonesia in CPO(Crude Palm Oil) export cooperation with Slovakia especially from the signing of theMemorandum of Understanding on Technical Cooperation in the Field of Agriculture in 2011.The method used in this research is qualitative research. Some of the data obtained camefrom books, journals, articles, annual reports, the internet and other media. In this study alsoused the perspective of liberalism, international cooperation theory, and national interestconcept.This research shows that Indonesia always faces the increasing of CPO exports to Slovakiaevery year, and Slovakia’s dependence to Indonesia’s CPO for the biofuel industries. ThenIndonesia makes Slovakia as a trading base to other European Union countries using the Port ofBratislava.Keywords: National Interests, CPO exports, Mou, Investment, Port of Bratislava